It's Getting Hot in Here: Piloting a Telemedicine OSCE Addressing Menopausal Concerns for Obstetrics and Gynecology Clerkship Students - Hadley W. Reid; Kelly Branford; Tracey Reynolds; Melody Baldwin; Sarah Dotters-Katz (MedEdPORTAL, 2021)
Introduction Although menopause is a common condition, trainees still express high levels of discomfort with managing climacteric symptoms. Trainees also receive little preparation for conducting telemedicine visits, which have become increasingly important in clinical care. We present a formative standardized patient (SP) encounter to introduce medical students to the diagnosis and treatment of menopausal symptoms and the process of conducting a telemedicine visit. Methods We designed a virtual telemedicine encounter with an SP for medical students. Students received feedback via a post-encounter note on history taking, differential diagnosis, and diagnostics/management and an SP debrief. We collected student input on the experience at the midpoint and end of clerkship and analyzed it for recurring themes. We calculated summary statistics from student post-encounter notes. Results Thirty-two OB/GYN students completed the menopause telemedicine SP encounter between April and June 2020. Students scored a median of 20 out of 45 (interquartile range: 18, 22) on the post-encounter note. All students correctly provided a diagnosis of perimenopause/menopause; however, 50% did not offer any strategy for counseling or managing menopausal symptoms. Students expressed discomfort with using a telehealth format (78%) but found it a useful skill to practice (47%). A majority (66%) found the educational encounter to be of excellent or above-average educational value. Discussion While medical students demonstrated discomfort with both managing menopause and utilizing a telemedicine format, this SP case provided an opportunity for them to practice both skills in a safe learning environment. The majority of participants rated the learning experience highly.